Analisis Yuridis Tentang Kewarganegaraan Anak Hasil Perkawinan Campuran Menurut Hukum Internasional dan Hukum Nasional - Nafna Dhini Harisha; Kharisma Kusuma Dewi; Hanifah Ramadani Oktafiani; Nur Sholikhah (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
Human mobility between countries has become an inevitable phenomenon in an increasingly open era of globalization. One of the tangible consequences of this mobility is the increasing number of mixed marriages between Indonesian citizens and foreign nationals. Although mixed marriages are a great way to interact across the globe, they often cause difficult legal problems, especially regarding the citizenship status of children born from these marriages. Children may be at risk of statelessness, or without citizenship, if the legal systems and principles between countries differ. This contradicts the principle of protection of human rights in international law. The purpose of this study is to examine the regulation of citizenship for children born to mixed marriages from an international law perspective. In addition, this study also investigates its relationship with Indonesian national law, particularly Law No. 12 of 2006 concerning Citizenship of the Republic of Indonesia and other related legal instruments. To gain a better understanding of the compatibility between national legal practices and international standards, a legislative, case, and comparative approach was used in this study. The results of the study show that, although Indonesia has adopted several principles of international law to prevent loss of citizenship and grant limited dual citizenship recognition to children born of mixed marriages, there is still a gap between the normative and its implementation. This discrepancy can lead to legal uncertainty and reduce the protection of children’s rights. In conclusion, this study emphasizes that national and international law in the field of citizenship must be harmonized to build a legal system that is responsive, fair, and in line with global societal progress, as well as to protect children’s rights at the international level.